Local Champion: A New Leadership Perspective to Create Sustainable Tourism in Rural Communities - Ginanjar, Retno; Riani, Asri Laksmi; Aini, Intan Novela Qurrotul (Eastasouth Institute, 2024)
UNWTO called 2017 the Year of Sustainable Tourism. In Indonesia, tourism growth is increasingly prominent, with a trend towards non-mainstream destinations. In 2022, interest in cultural immersion will increase, as evidenced by the development of dozens of tourist villages. Rural tourism has a substantial role in the economy and tourist sector, exerting a favorable influence on economic expansion, population stability, and the enhanced worth of indigenous goods. Rural tourism is a sustainable development strategy, including cultural conservation, natural resources and community empowerment. The Indonesian Ministry of Tourism and Creative Economy is targeting 224 independently certified tourist villages by 2024. The Community Based Tourism (CBT) approach is used in managing tourist villages to achieve sustainable tourism. Ministerial Regulation Number 9 of 2021, which outlines the Guidelines for Sustainable Tourism Destinations, demonstrates Indonesia's dedication to promoting sustainable tourism. Although rural tourism can provide economic benefits, effective leadership is required for competitive and sustainable development. A